Employing Artificial Intelligence in TV Newsrooms: Build an applied model - Hamza Khaled Mutshar, Asst. Lecturer (lark, 2026)
The topic and research of AI is one of the important topics and research in the field of television newsrooms, due to the importance and benefit of employing these technologies and programs for the purpose of carrying out some of the tasks and functions carried out by workers in television newsrooms. Therefore, the research problem was embodied in the issue of employing AI in television newsrooms, and it aims to reveal the mechanisms for satellite channels adopting AI in newsrooms, and to build an application model for Iraqi TV. This research is descriptive, and the researcher relied on the case study approach through a theoretical introduction to the topic of employing AI in television newsrooms. After that, several applied models on the subject were reviewed, and an applied model for research was formulated that could be applied in Iraqi TV. The study reached several results, the most notable of which are: TV International rely on AI in newsrooms to detect Deepfake and manipulation of information and data. The study presents the possibility of benefiting from deep learning techniques, natural language understanding techniques, and huge data and information processing. AI has the ability to compose and write texts and news stories, and this makes it useful in newsrooms through connect it with news agencies.